PROPRIEDADES ESTRUTURAIS, MECÂNICAS E BIOATIVAS DAS LIGAS DE CoCr DOPADOS COM B e Ta, DE INTERESSE PARA APLICAÇÕES BIOMÉDICAS - SANTOS, Emanuella Fabrícia Carvalho dos (2020)
In this study new Co-Cr alloys were synthesized using Boron (B) and Tantalum (Ta) as alloying elements, in the compositions (Co1-xTax)0.72Cr0.28 with x = 0, 0.02, 0.04, 0.06 and 0.1 and Co0.71Cr0.29By with y = 0.02 and 0.04%, with mass concentrations. The stoichiometric quantities of each sample were arc melted, under an argon atmosphere, and subsequently thermal annealing. X-ray Diffraction (XRD) measurements and Rieltveld refinement analysis show that Co0.72Cr0.28 sample crystallize with the Co compact hexagonal structure (Co phase, space group P63 / mmc) and Co0,23Cr0,77 secondary phase with the tetragonal structure ( phase, space group P42/mnm). B or Ta addition induces secondary phases such as Cr2B and Co2Ta, respectively, concomitantly reduces the  phase fraction. B atoms possibly occupying interstitial position induces Co unit cell volume expansion of ~ 1%. On the other hand, an expansion of ~ 3.1% in the Co phase unit cell volume is observed for Ta doped samples (except for Ta6 sample) possibly because Ta atoms are 19% bigger then Co atoms. The alloys average density oscillates between 7.3 and 8.7 g/cm3 . The presence of alloying elements Ta or B increases the samples Vickers hardness by 33% (for x = 0.06) and 100% (for y = 0.04), respectively. Atomic Force Microscopy measurements show precipitates on the samples surface. The high roughness values were observed for samples with boron 2% and tantalum 6%. The alloy with boron 4% shows greater interaction with the SBF in the first 120 minutes of exposure. Scanning Electron Microscopy (SEM) measurements showed different microstructures over the alloys surface, while Energy Dispersive Spectroscopy (EDS) measurements indicate O, Ca, O, P, Cl, Na and traces of Mg and S elements in some regions, showing the presence of ions expected for biological apatite. XRD results after SBF test shown diffraction peaks around 31.5 degree indicating hydroxyapatite presence in the sample surface. This study provides evidence that Ta and B alloy elements improve mechanical and bioactivity properties of the CoCr alloy. This study provides evidence that the elements Ta or B improve the mechanical properties and favored the bioactivity of Co-Cr-B and Co-Cr-Ta alloys.